LAW ENFORCEMENT AGAINST HUMAN TRAFFICKING CRIMES (STUDY AT ASAHAN POLICE) - Dessy Dara Lampabe; Rizkan Zulyadi; Serimin Pinem (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study analyzes human trafficking (TPPO) in Asahan Regency during the period 2018–2023, focusing on modus operandi, criminal policies, and enforcement obstacles. The study employs a normative legal research method, using library research and analysis of legislation, official police documents, annual reports, and scholarly literature related to TPPO. The results indicate that TPPO modus operandi has evolved from traditional methods to modern forms that utilize technology, social media, and cross-regional networks. Perpetrators carry out various actions, including recruiting migrant workers without authorization, document forgery, domestic exploitation, and child exploitation in the plantation sector. These crimes emphasize economic and sexual exploitation of vulnerable groups, particularly women and children, and exploit victims’ lack of knowledge regarding legal procedures and legal migration. TPPO handling in Asahan Regency is conducted through a combination of penal and non-penal strategies. The penal approach emphasizes firm law enforcement oriented toward victims, through enhanced investigator capacity, establishment of special units, actions against organized networks, and optimization of asset seizure. The non-penal approach focuses on prevention through public education, awareness campaigns on illegal recruitment methods, strengthening community networks, monitoring high-risk areas, and providing integrated services for victims. However, law enforcement faces various structural, procedural, social, and institutional obstacles, including limited resources, low public legal awareness, victim trauma, and the complexity of transnational and covert modus operandi. To enhance the effectiveness of TPPO enforcement, a comprehensive strategy is required, including strengthening law enforcement capacity, providing adequate victim protection systems, implementing preventive policies based on education and community empowerment, fostering multi-stakeholder collaboration, and conducting continuous monitoring and evaluation of emerging forms of TPPO.